Peran Orang Tua Dalam Pendidikan Agama Anak - Mubiarto, Akhli Nur (Early Childhood Research and Practice, 2025)
Religious education is one of the important aspects in shaping children's character. The role of parents as primary educators is very significant in instilling religious values from an early age. This article discusses the role of parents in children's religious education, including their responsibilities, strategies and challenges. Using the literature review method, this article reveals the importance of active involvement of parents in educating children religiously in order to create a generation of faith and noble character. The results of the study show that the success of children's religious education is strongly influenced by consistency, exemplification, and communication carried out by parents in the family environment.